Clinical profile and outcomes in patients with moderate to severe aortic stenosis with or without concomitant chronic kidney disease - Jinghao Nicholas Ngiam; Ching-Hui Sia; Nicholas Wen Sheng Chew; Tze Sian Liong; Zi Yun Chang; Chi Hang Lee; Wen Ruan; Edgar Lik-Wui Tay; William Kok-Fai Kong; Huay Cheem Tan; Tiong-Cheng Yeo; Kian Keong Poh (Singapore Medical Journal)
Introduction: Management of aortic stenosis (AS) in patients with chronic kidney disease (CKD) may often be overlooked, and this could confer poorer outcomes. Methods: Consecutive patients (n = 727) with index echocardiographic diagnosis of moderate to severe AS (aortic valve area <1.5 cm2) were examined. They were divided into those with CKD (estimated glomerular filtration rate < 60 mL/min) and those without. Baseline clinical and echocardiographic parameters were compared, and a multivariate Cox regression model was constructed. Clinical outcomes were compared using Kaplan–Meier curves. Results: There were 270 (37.1%) patients with concomitant CKD. The CKD group was older (78.0 ± 10.3 vs. 72.1 ± 12.9 years, P < 0.001), with a higher prevalence of hypertension, diabetes mellitus, hyperlipidaemia and ischaemic heart disease. AS severity did not differ significantly, but left ventricular (LV) mass index (119.4 ± 43.7 vs. 112.3 ± 40.6 g/m2, P = 0.027) and Doppler mitral inflow E to annular tissue Doppler e’ ratio (E: e’ 21.5 ± 14.6 vs. 17.8 ± 12.2, P = 0.001) were higher in the CKD group. There was higher mortality (log-rank 51.5, P < 0.001) and more frequent admissions for cardiac failure (log-rank 25.9, P < 0.001) in the CKD group, with a lower incidence of aortic valve replacement (log-rank 7.12, P = 0.008). On multivariate analyses, after adjusting for aortic valve area, age, left ventricular ejection fraction and clinical comorbidities, CKD remained independently associated with mortality (hazard ratio 1.96, 95% confidence interval 1.50–2.57, P < 0.001). Conclusion: Concomitant CKD in patients with moderate to severe AS was associated with increased mortality, more frequent admissions for cardiac failure and a lower incidence of aortic valve replacement.